2014
DOI: 10.1016/j.ibmb.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Manduca sexta proprophenoloxidase activating proteinase-3 (PAP3) stimulates melanization by activating proPAP3, proSPHs, and proPOs

Abstract: Melanization participates in various insect physiological processes including antimicrobial immune responses. Phenoloxidase (PO), a critical component of the enzyme system catalyzing melanin formation, is produced as an inactive precursor prophenoloxidase (proPO) and becomes active via specific proteolytic cleavage by proPO activating proteinase (PAP). In Manduca sexta, three PAPs can activate proPOs in the presence of two serine proteinase homologs (SPH1 and SPH2). While the hemolymph proteinases (HPs) that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…Protease cascades in M. sexta hemolymph have been extensively investigated through reconstitution of pathways using purified natural and recombinant proteins and by ex vivo analysis of proteins added to hemolymph plasma (An et al, 2009; Gorman et al, 2007; Jiang, 2008; Kanost et al, 2004; Wang and Jiang, 2007, 2008; Wang et al, 2014). In the current studies, we found that serine proteases and catalytically inactive pseudoproteases, termed serine protease homologs (SPH), are encoded by 193 genes in M. sexta .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protease cascades in M. sexta hemolymph have been extensively investigated through reconstitution of pathways using purified natural and recombinant proteins and by ex vivo analysis of proteins added to hemolymph plasma (An et al, 2009; Gorman et al, 2007; Jiang, 2008; Kanost et al, 2004; Wang and Jiang, 2007, 2008; Wang et al, 2014). In the current studies, we found that serine proteases and catalytically inactive pseudoproteases, termed serine protease homologs (SPH), are encoded by 193 genes in M. sexta .…”
Section: Resultsmentioning
confidence: 99%
“…Pathways of clip domain proteases and SPHs (acting as cofactors with poorly understood molecular function) that activate proPO and the Toll ligand spaetzle have been identified in M. sexta hemolymph, involving 6 clip SPs and 2 SPHs (Fig. 9) (Kanost and Nardi, 2010; Wang et al, 2014). Sequence alignment and phylogenetic analysis revealed evolutionary relationships among the clip-domain proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative and more parsimonious explanation is that CLIPB8 is required for the activation of one or several proteolytically inactive CLIPAs that complement the proPO cascade. Published examples for proteolytic activation of CLIPAs by CLIPBs exist from other insect species (Kan et al, 2008; Wang et al, 2014). A candidate for such a proteinase homolog is CLIPA8, which is required for melanization of bacteria, fungi and P. berghei (Schnitger et al, 2007; Volz et al, 2006; Yassine et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the proteomic analysis of larval hemolymph, we identified 36 SPs and SPHs, nine of which are known to be components of the SP-SPH system (Zhang et al, 2014; He et al, 2016). They are: HP14 (HP for hemolymph protease), HP21, HP6, HP8, proPO activating proteases (PAP1–3), SPH1, and SPH2 (Jiang et al, 2010; Wang et al, 2014). We isolated SP and SPH cDNAs (or genes) from hemocytes or fat body for HP1–4, PAP1–3, HP5–24, SPH1, and SPH2 (Jiang et al, 1998, 1999, 2003a, 2003b and 2005; Wang et al, 2006; Yu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%